Pengaruh Aplikasi AI terhadap Motivasi dan Keterlibatan Siswa SMP NU Medan - Saiful Amir; Nurul Ajima Ritonga (Journal on Education, 2024)
Motivation and student engagement in learning pose challenges faced by many schools, including SMP NU Medan. The lack of interest and participation among students hinders the learning process. With the development of artificial intelligence (AI)-based applications, there is potential to support learning and enhance student motivation and engagement. The aim of this research is to analyze the impact of using AI applications on the motivation and engagement of students at SMP NU Medan. This study employs a quantitative approach with an experimental method. A total of 36 ninth-grade students were selected through purposive sampling, and data were collected using a Likert scale questionnaire, analyzed using descriptive statistical tests, Pearson correlation, reliability, and homogeneity tests. The results indicate a significant positive relationship between the use of AI applications and student motivation, with a correlation value of r = 0.320 (p < 0.05). However, the relationship between the use of AI applications and student engagement showed a lower strength, with a correlation value of r = 0.181 (p < 0.05). Descriptive analysis revealed an average motivation score of 19.42 and an engagement score of 18.89, indicating that the majority of students have a fairly good level of motivation and engagement.